2018
DOI: 10.1007/s40430-018-1235-0
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study on the dry sliding wear behaviour of AA6082–T6/TiB2 in situ composites using response surface methodology

Abstract: Present work deals with the parametric study of dry sliding wear behaviour of TiB 2-reinforced aluminium matrix composites (AMCs). Aluminium 6082-T6 alloy specimens reinforced with 0, 3, 6, 9 and 12 wt% of TiB 2 particles were fabricated by the in situ reaction of K 2 TiF 6 and KBF 4 in heated liquid aluminium. Experiments were conducted to study the wear behaviour of AA6082-T6/TiB 2 composites using pin-on-disc apparatus at room temperature. Weight percentage of reinforcement, sliding speed, load and sliding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Particulate-reinforced aluminium matrix composites (PRAMCs) have wide applications in automobiles and railway vehicles parts due to their superior tribological properties than un-reinforced alloys [1][2][3]. PRAMCs reinforced with single reinforcement generally exhibit marginal improvement in wear resistance as compared to base alloy [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particulate-reinforced aluminium matrix composites (PRAMCs) have wide applications in automobiles and railway vehicles parts due to their superior tribological properties than un-reinforced alloys [1][2][3]. PRAMCs reinforced with single reinforcement generally exhibit marginal improvement in wear resistance as compared to base alloy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple particulate reinforcements in the PRAMCs improve wear resistance extensively. Different materials have been synthesized by multiple reinforcements with promising results [6][7][8][9], but the work is limited with Al 3 Zr and ZrB 2 combination [1,[10][11][12]. The Al 3 Zr exhibits low density, high melting point and high elastic modulus with excellent resistance to oxidation and corrosion [2].…”
Section: Introductionmentioning
confidence: 99%
“…However literature suggests that particle agglomeration can enhance composite's performance when well bonded with the matrix. 18 Figure 7(e) shows the SEM micrograph of Al2024-9% TiB 2 composite (at higher magnification). Figure 7(e) depicts that the shape of TiB 2 particles are hexagonal or spherical.…”
Section: Sem Analysismentioning
confidence: 99%
“…Compared to other ceramic reinforcements, titanium diboride emerged to be the most promising reinforcement as no detrimental by-product is formed between the matrixreinforcement interfaces and excellent interfacial bonding is achieved which contributes to the improvement in mechanical properties of the prepared AMCs. 18 Fabrication of AMCs can be accomplished by different techniques viz. stir casting, friction stir processing, powder metallurgy and severe plastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [ 26 ] studied the dry sliding wear behaviour of AA6082–T6/TiB 2 in situ composites using response surface methodology. Yasir et al [ 27 ] studied SiC and alumina reinforced Al 6061 fusion composite and reported that the wear resistance of 15 wt.% filler reinforced hybrid composite is better than that of 5 wt.% filler reinforced composite. Zhu et al [ 28 ] conducted a drilling of aluminum 2024-T351/titanium Ti6Al4V stack and studied the mechanism of chip formation.…”
Section: Introductionmentioning
confidence: 99%